MEDIA PEMBELAJARAN INTERAKTIF BERBASIS VIRTUAL REALITY MENGGUNAKAN VIDEO 360° - Ashafidz Fauzan Dianta; Citra Devi; Widi Sarinastiti; Zulhaydar Fairozal Akbar (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
Learning media is currently required to keep up with the rapid development of information technology. Interactive learning media present the delivery of material that users can not only see and hear, but to which they can also actively respond. The characteristics of interactive learning media require users to always interact during the learning process so as to foster a positive attitude among users towards learning. 360° video is a technology that can visualize the entire point of view that is around us. Content generated from 360° videos can create immersive virtual reality experiences. The purpose of this research is to create an interactive learning medium based on 360° video as a learning resource for students to learn the tools commonly used to produce TV programs, namely the Blackmagic Design Studio camera and the Atem Mini Switcher. The research method used is the Villamil-Molina method, here are the stages: 1. Development; 2. Preproduction; 3. Produc-tion; 4. Postproduction; and 5. Delivery. The results of this study indicate that it has succeeded in accordance with its functionality in making interactive learning media based on virtual reality using 360° video as an alternative media for student learning resources to learn tools commonly used in TV studio courses.